Selective laser sintering of bonded magnets from flake and spherical powders. (November 2019) - Mapley, Martin; Pauls, Jo P.; Tansley, Geoff; Busch, Andrew; Gregory, Shaun D.
Abstract: The use of additive manufacturing (AM) techniques for low volume production of complex geometries from a wide range of materials has shown to decrease product cost and lead times. This work describes the production of net-shaped bonded NdFeB magnets using selective laser sintering (SLS) from mechanically mixed isotropic powders. Magnets were produced from magnetic powders with both flake and spherical particle morphologies and were shown experimentally to possess magnetic properties comparable to permanent magnets produced using other AM methods (residual induction of 302 and 362 mT, intrinsic coercivity of 661 and 735 kA/m for flake and spherical powders respectively). Graphical abstract: Scanning electron microscope images of NdFeB (a) flakes and (b) spheres suspended in the polyamide-12 matrix with (c) a magnetic impeller produced using selective laser sintering. Demagnetisation curves of the starting powders at their theoretical density and the produced parts are shown in (d).Unlabelled Image